Midwives' insights in relation to the common barriers in providing effective perinatal care to women from ethnic minority groups with 'high risk' pregnancies: A qualitative study. Issue 2 (March 2022) - Chitongo, Sarah; Pezaro, Sally; Fyle, Janet; Suthers, Fiona; Allan, Helen
Abstract: Problem: Childbearing women from ethnic minority groups in the United Kingdom (UK) have significantly poorer perinatal outcomes overall. Background: Childbearing women from ethnic minority groups report having poorer experiences and outcomes in perinatal care, and health professionals report having difficulty in providing effective care to them. Yet barriers in relation to providing such care remain underreported. Aim: The aim of this study was to elicit midwives' insights in relation to the common barriers in providing effective perinatal care to women from ethnic minority groups with 'high risk' pregnancies and how to overcome these barriers. Methods: A qualitative study was undertaken in a single obstetric led unit in London, UK. A thematic analysis was undertaken to identify themes from the data. Findings: A total of 20 midwives participated. They self-identified as White British (n = 7), Black African (n = 7), Black Caribbean (n = 3) and Asian (n = 3). Most (n = 12) had more than 10 years' experience practising as a registered midwife (range 2 – 35 years). Four themes were identified: 1) Communication, 2) Continuity of carer, 3) Policy and 4) Social determinants. Racism and unconscious bias underpin many of the findings presented. Discussion: Co-created community hubs may improve access to more effective care for childbearing women from ethnic minority groups. A focus on robust anti-racism interventions, continuity of carer, staff wellbeing and education along with the provision of orientation and bespoke translation services are also suggested for the reduction of poorer outcomes and experiences. Conclusion: Along with policies designed to promote equality and irradicate racism, there is a need for co-created community hubs and continuity of carer in perinatal services. Further research is also required to develop and evaluate culturally safe, and evidence-based interventions designed to address the current disparities apparent.